Analysis of the Optical Properties of Medieval Enamel - Ljiljana Tihaček-Šojić; Marija Đurić-Srejić (Dental Anthropology Association, 1998)
The purpose of the study was to investigate the differences in the optical properties of samples of intact, abraded, and reduced enamel. The optical properties of medieval enamel were compared to the results obtained from studies of enamel of contemporary populations in order to investigate the structural changes of enamel due to the effect of diagenesis (destructive changes, which affect interred bone). Reduced enamel (artificially removed superficial layer of the enamel) was used as a comparative sample for the study of abraded enamel. The dental material was obtained from the medieval cemetery of Stara Torina located in northern Serbia. Micro-morphological analysis was conducted using a polarized light microscope. Based on the results, we can demonstrate that 1) the birefringence value of the mature medieval enamel sample ranges from 0.3 to 0.4, which means that medieval enamel has retained its optical properties, although some changes in the inorganic components were found; 2) the mature intact enamel and abraded enamel have a negative optical sign, which is the same as that found in immature enamel; and 3) the mature reduced enamel changes its optical sign due to the phenomena of bending of the surface enamel prisms from 0.7 mm to 0.9 mm. This change of the optical sign results from a rise in temperature during the reduction process and from a diffusion of "non-oriented" molecules. The increased pressure on the enamel during the reduction process causes the bending of the surface part of the enamel prisms. The presence of the pigmentation and carious changes in the abraded enamel and ground enamel also indicated the process of diffusion of different molecules, which occurred while the enamel was buried in the soil, as well as during the lifetime of the individual.